Performance Characteristics of Vortex Wind Turbines with The Computational Fluid Dynamics (CFD) Aided Simulation - Rusianto Toto; Sudarsono; Kristiyana Samuel; Purwanto Yuli (E3S Web of Conferences)
The purpose of this paper present research on vortex wind turbines that is referred to as wind turbines without propellers or bladeless. The innovation of the vortex lies in its unique shape and the way it harnesses energy through oscillating motion. The mast column oscillates with the wind, harnessing the von Karman vortices generated as the fluid passes through the column structure. This paper presents the results of computational fluid dynamics (CFD) simulations of a vortex wind turbine with 6 and 7 inch diameter cylinders at various wind speeds. The voltage generated by a vortex wind turbine with a cylinder diameter of 6 inches was measured under realistic conditions to evaluate the wind turbine’s performance in terms of output power generator due to vortex generation. The result of the research show wind speeds as low as 5 m/s that the vortex wind turbines may already exhibit generator-induced oscillations. Vibrations can be obtained using either CFD simulations or measurement results in actual conditions that the vibrations can generate a generator to produce electric voltage.